Peningkatan Kewirausahaan Melalui Buket Bunga Pada Perempuan Rawan Sosial Ekonomi di YAFSI - Ramadhan Lubis, Rafi; Utama Ritonga, Fajar; Thamrin, Thamrin (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
This research explores the impact of giving a bouquet of flowers to women who are in a socio-economically vulnerable condition, in the rapid development of the times that makes changes throughout the scope of human life. Ineffective waste management can lead to various environmental problems, including soil and water pollution and can cause pollution that is harmful to the community. This study aims to explore creative approaches in recycling plastic and paper waste by making flower bouquets. Not only does this approach reduce the volume of waste, it also raises awareness to the community about the importance of recycling and creativity in waste management. The study concluded that making flower bouquets from plastic and paper waste not only contributes to waste reduction, but also opens up economic opportunities for clients through creative industries